44.2k views
3 votes
(x + 2)(x(square)+ x + 1)

Explain it steps

2 Answers

3 votes

Answer:


{x}^(3) + 3 {x}^(2) + 3x + 2

Explanation:


(x + 2)( {x}^(2) + x + 1)


= x( {x}^(2) + x + 1) + 2( {x}^(2) + x + 1)


= {x}^(3) + {x}^(2) + x + 2 {x}^(2) + 2x + 2


= {x}^(3) + 3 {x}^(2) + 3x + 2

User Jay Askren
by
5.1k points
2 votes

Answer:

x= 2

x= 1-√-3/2

x = 1+√-3/2

Explanation:

(x+2)(x²+x+1) =(x³+x²+x+2x²+2x+2)

(x³+3x²+3x+2)

User Tom Lianza
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.